2021
DOI: 10.1021/acsami.1c12438
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing, Self-Adhesive Strain Sensors Made with Carbon Nanotubes/Polysiloxanes Based on Unsaturated Carboxyl–Amine Ionic Interactions

Abstract: Strain sensors with high sensitivity, long-term durability, and stretchability are required for flexible and wearable electronic devices. This paper reports a bilayer strain sensor consisting of carboxyl-functionalized carbon nanotubes (CNTs) and ionically crosslinked polysiloxane substrates based on unsaturated acid–amine interactions. Vacuum filtration was adopted to prepare the CNT films (2.74–4.70 μm in thickness) onto the polysiloxane substrates to prepare stretchable conductive strain sensors. The strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 71 publications
0
28
1
Order By: Relevance
“…Increased material strength was observed in reinforced systems while surprisingly maintaining similar strain to the unreinforced material, implying that there was no significant loss in material extensibility despite the integration of MWCNTs. This is unlike most of the previously reported self-healing polymer nanocomposites that give increased strength with a trade-off in decreased elongation, which means the ability of a material to achieve a certain amount of strain. , …”
Section: Introductioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Increased material strength was observed in reinforced systems while surprisingly maintaining similar strain to the unreinforced material, implying that there was no significant loss in material extensibility despite the integration of MWCNTs. This is unlike most of the previously reported self-healing polymer nanocomposites that give increased strength with a trade-off in decreased elongation, which means the ability of a material to achieve a certain amount of strain. , …”
Section: Introductioncontrasting
confidence: 67%
“…40 Generally, since electrical percolation is less impacted by chain bridging in polymer architecture, all DPNs in this study showed electrical conductivities in the order of 10 −5 −10 −4 S/m due to only less than 1 wt % MWCNT nanoreinforcement (Figure 7f), suggesting that these DPNs could potentially contribute to the rapidly growing fields of flexible compliant electrodes 65 and strain sensors. 45 In the future, scientists envisage that human senses will be greatly enhanced by electronics that are built into accessories, clothes, and sensors attached to the skin. This has influenced the high demand in wearable electronics such as flexible compliant electrodes 66 and strain sensors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kang et al placed a molybdenum intermediate layer between the conductive and substrate layers to enhance cohesion among different layers . Also, Zhang et al prepared a self-healing strain sensor fabricated by carbon nanotubes/polysiloxanes based on unsaturated carboxyl–amine ionic interactions to improve durability . Although the advanced functional materials of the above work indeed play a positive role in improving the sensor performance, they are too expensive and require a complex fabricating process.…”
Section: Introductionmentioning
confidence: 99%